Population Analysis of O26 Shiga Toxin-Producing Escherichia coli Causing Hemolytic Uremic Syndrome in Italy, 1989–2020, Through Whole Genome Sequencing - Michelacci, Valeria; Montalbano Di Filippo, Margherita; Gigliucci, Federica; Arancia, Silvia; Chiani, Paola; Minelli, Fabio; Roosens, Nancy H. C.; De Keersmaecker, Sigrid C. J.; Bogaerts, Bert; Vanneste, Kevin; Morabito, Stefano (Frontiers in Cellular and Infection Microbiology, 2022)
Shiga toxin-producing Escherichia coli (STEC) belonging to the O26 serogroup represent an important cause of Hemolitic Uremic Syndrome (HUS) in children worldwide. The localization of STEC virulence genes on mobile genetic elements allowed the emergence of clones showing different assets of this accessory genomic fraction. A novel O26 STEC clone belonging to Sequence Type (ST) 29 and harboring stx2a, ehxA and etpD plasmid-borne genes has emerged and spread in Europe since the mid-1990s, while another ST29 clone positive for stx2d and lacking plasmid-borne virulence genes was recently described as emerging in France. In Italy, O26 has been the most frequently detected STEC serogroup from HUS cases since the late 1990s. In this study we describe the genomic characterization and population structure of 144 O26 STEC strains isolated from human sources in Italy in the period 1989-2020. A total of 89 strains belonged to ST21, 52 to ST29, two to ST396 and one to ST4944. ST29 strains started to be isolated from 1999. 24 strains were shown to harbour stx1a, alone (n=20) or in combination with stx2a (n=4). The majority of the strains (n=118) harbored stx2a genes only and the two ST396 strains harbored stx2d. A Hierarchical Clustering on Principal Components (HCPC) analysis, based on the detection of accessory virulence genes, antimicrobial resistance (AMR) genes and plasmid replicons, classified the strains in seven clusters identified with numbers from 1 to 7, containing two, 13, 39, 63, 16, 10 and one strain, respectively. The majority of the genetic features defining the clusters corresponded to plasmid-borne virulence genes, AMR genes and plasmid replicons, highlighting specific assets of plasmid-borne features associated with different clusters. Core genome Multi Locus Sequence Typing grouped ST21 and ST29 strains in three clades each, with each ST29 clade exactly corresponding to one HCPC cluster. Our results showed high conservation of either the core or the accessory genomic fraction in populations of ST29 O26 STEC, differently from what observed in ST21 strains, suggesting that a different selective pressure could drive the evolution of different populations of these pathogens possibly involving different ecological niches.